Tax Treatment of Private Pension Savings in OECD Countries and the Net Tax Cost Per Unit of Contribution to Tax-Favoured Schemes - Yoo, Kwang-Yeol (OECD Publishing, 2004)
This paper provides, for all OECD countries, an estimate of the net tax cost per currency unit of contribution to a tax-favoured retirement savings plan, using a present-value methodology. The latter takes into account the future flows of revenues foregone on accrued income and of revenues collected on benefit withdrawals corresponding to a unit contribution made in a given year. The net tax cost is first calculated for nine (five-year) age groups, which have different relative income levels and investment time horizons, and is then averaged across age groups. In order to take into consideration the relevant country-specific features of savings taxation, the paper also provides an overview of the tax treatment of private pension arrangements and alternative savings vehicles. The results indicate that the size of tax subsidy varies significantly across countries, ranging from nearly 40 cents per unit of contribution (Czech Republic) to around zero (Mexico, New Zealand). Over half of ...
Keywords: Economics